ASSESSMENT OF HEALTH CARE WASTE MANAGEMENT COMPLIANCE IN THE NORTHERN CAPE DEPARTMENT OF HEALTH - MOTLATLA, MOKETE FRANS (Bloemfontein: Central University of Technology, Free State, 2015)
Poor handling of health care waste has posed many adverse health effects for health care workers, the general public and the environment. The vastness of the Northern Cape Province has directly impacted negatively on the poor performance of health care facilities, particularlyin terms of health care waste management. Public health care facilities in the region are the major generators of health care waste (HCW) in the Northern Cape Province. This study reports on the assessment of the HCW management practices in terms of the health care waste life cycle within the Northern Cape Department of Health (South Africa). The results of the assessment were compared with applicable legislative requirements and global practices in HCW management. The study was conducted in five districts of the Northern Cape Department of Health and 11 hospitals were selected randomly as study sites from a total of 17 hospitals. Data obtained from the service provider wereused to determine the quantities of the health waste at each study site. Interviews using a structured questionnaire were also used to assess the knowledge and practices of HCW handlers. An estimated 16 070 kg of health care waste was generated by 36 437 patients per month at the 11 surveyed hospitals. The survey illustrated that the main health care waste types generated in the hospitals were general infectious waste, sharps waste, anatomical waste and pharmaceutical waste. It was concluded that the heath care waste management practices in the hospitals in the Northern Cape Department of Heath, South Africa, did not meet the recommended standards for the management of HCW as recommended by the World Health Organisation (WHO). There was a very low prioritisation of HCW management by top management. Inadequate human and financial resources allocated for HCW management were highlighted. Complete health care waste management requires adequate resource allocation and appropriate support from senior management within the Northern Cape Department of Health. Reprioritisation of funding and human resources towards HCW management in all health care facilities is required to improve the environment and make it safe for humans and animals.
Thesis